Mind wandering is not always harmful in sports: the role of its content - Li, Jieling; Li, Chuangye; Xue, Shuangpeng; He, Yuxiu (Frontiers in Psychology, 2024)
Objective Mind wandering (MW) among athletes during training and competition can lead to poor performance. However, MW has also been found to have positive effects. This study aims to clarify the causes of the bidirectional (negative and positive) effects of MW in the sports context, specifically focusing on whether these effects are related to the content of MW. Methods A total of 846 Chinese athletes completed the Chinese version of the MW scales. The survey data were tested for common method biases. Subsequently, Pearson correlation analysis and structural equation modeling were performed using SPSS 25.0 and Mplus 7.0. Results The frequency of MW can positively predict its bidirectional effects. MW content plays an important role in the relationships between MW frequency and its negative and positive effects, but the direction of influence varies depending on the content. Conclusion MW in sports is not always harmful, and its content plays an important role. These findings suggest that managing MW content may be a promising MW intervention method for improving performance in sports.